Identification of microbiota in peri-implantitis pockets by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry - Hwey-Chin Yeh (Nature Portfolio, 2019)
Abstract The purpose of this study was to identify the microbial communities that colonize peri-implantitis pockets using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Subjects having at least one implant with peri-implantitis, no diabetes, and not taking antibiotics in the previous 3 months were selected. Peri-implantitis was defined when surrounding bone loss ≥0.5 mm and bleeding on probing was found. Microbial samples were collected from peri-implantitis pockets using paper points. After incubation and isolation, the colonies were analyzed by MALDI-TOF MS. A total of 126 isolates were cultivated and identified from 12 samples, in identification rates of 82.5% at the species level and 12.72% at the genus level. Although the compositions were highly variable, major habitants in different peri-implant pockets could be identified. Among them the most distinguished were Neisseria flavescens (87%), Streptococcus constellatus (56%), Slackia exigua (46%), Streptococcus intermedius (45%), Fusobacterium nucleatum (45%) and Gemella morbillorum (43%). This preliminary study provides comprehensive and reliable data for future study designs involving MALDI-TOF MS and peri-implantitis in a more specific, easy, rapid and economical way. MALDI-TOF MS could be a new clinical method to evaluate and monitor oral microbiota associated with the disease.